Test Method for the Presence or Absence of Pb in Electrical Components Using Energy-Dispersive Micro X-ray Fluorescence - ARAKI, Wakako; MIZOROKI, Kaoru; OKI, Mitsuhiro; TAKENAKA, Miyuki (Analytical Sciences, 2005)
The μ-EDXRF (energy dispersive X-ray fluorescence) method was applied to the screening of Pb in micrometer-area samples, such as a Cu contact in electrical components that had been coated by Pb-free Sn-Ag-Cu solder. The reliability of the screening method was evaluated by a comparison with a scanning electron microscope (SEM) observation and a precious chemical analysis method of inductively coupled plasma mass spectrometry (ICP-MS). Some factors that affect the testing reliability, such as the thickness of the solder, the segregation of Pb and Ag, etc. were found by SEM observations. By adjusting some calculation parameters, screening of the micrometer area (0.1 mm) was performed using the fundamental parameter (FP) method for a thin film in conjunction with μ-EDXRF. The measurement error ranged by 25% for the thin film-FP method. The resulted detection limit was 0.04 wt% for Pb, depending on the solder thickness. This method can be successively applied for quality control to check the purity of a Pb-free Sn-Ag-Cu solder coating in electrical components.